What forage tree-shrub species are recommended in alley cropping systems under west Asia conditions? - Louhaichi, Mounir; Hassan, Sawsan (International Center for Agricultural Research in the Dry Areas, 2022)
Presentation about the using suitability index based on growth characteristics to evaluate the performance of various shrubs as potential hedgerow species for alley cropping systems under west Asia conditions. Seven shrubs' species were evaluated in this study including three leguminous forage species (Medicago arborea, Colutea istria and Coronilla glauca), three Atriplex species (A. canescens, A. nummularia, A. undulata) and spineless cactus pear (Opuntia ficusindica) intercropped between annual crops of wheat, vetch and barley at the Mushaqqar Research Station in Jordan. Results should that Atriplex species (A. canescens) performed well and can be an ideal species for establishing alley cropping under WA conditions. The multiple benefits of alley cropping can only strengthen resilience of the production system to sustain livelihood of the agrosilvopastoral communities. This presentation was performed during the 5th World Congress on Agroforestry: “Transitioning to a Viable World”. Québec, Canada, July 17-20, 2022.